PROFITABILITAS DAN NILAI TAMBAH AGROINDUSTRI OLAHAN IKAN LELE DI KECAMATAN METRO SELATAN KOTA METRO - Syendita Dwi Cahyahati; Ktut Murniati; Zainal Abidin (Lampung University, 2019)
This study aims to analyze profitability and added value of catfish processing products. This research is case studies on La Tansa, Oseri and Osta Food Agroindustry for the reason of that catfish processing products are one of the regional superior products in Metro City. The study was conducted in February-March 2018 in which data was analyzed by quantitative analysis. The results showed that profitability ratios obtained by La Tansa Agroindustry was 48.27% in abalone catfish products and 23.58% in catfish bone crackers products. Whereas the profitability ratios of Agroindustry Oseri amounted to 51.14% in abalone catfish products and 34.62% in catfish bone crackers products. The revenue from the total cost per month in La Tansa Agroindustry was Rp2,174,546.67 on abalone catfish products and Rp518,161.67 in catfish bone crackers products. Whereas, Agroindustry Oseri Rp5,617,646.62 on abalone catfish products and Rp2,188,286.71 on catfish bone crackers products. Both agroindustry were feasible because they had positive added value and were profitable because the R / C ratio was more than one. Key words : added value, agroindustries, catfish, profitability